Development and Validation of a Personalized Survival Prediction Model for Uterine Adenosarcoma: A Population-Based Deep Learning Study - Qu, Wenjie; Liu, Qingqing; Jiao, Xinlin; Zhang, Teng; Wang, Bingyu; Li, Ningfeng; Dong, Taotao; Cui, Baoxia (Frontiers in Oncology, 2021)
Background: The aim was to develop a personalized survival prediction deep learning model for adenosarcoma patients using the surveillance, epidemiology and end results (SEER) database. Methods: A total of 797 uterine adenosarcoma patients were enrolled in this study. Duplicated and useless variables were excluded, and 15 variables were selected for further analyses, including age, grade, lymph nodes, marital status, race, tumor extension, stage, and surgery. We created our deep survival learning (DSL) model to manipulate the data, which was randomly split into a training set (n=519, 65%), validation set (n=143, 18%) and testing set (n=143, 18%). The Cox proportional hazard (CPH) model was also included comparatively. Finally, personalized survival curves were plotted for randomly selected patients. Results: The c-index for the CPH model was 0.726, and the Brier score was 0.17. For our deep survival learning model, we achieved a c-index of 0.774 and a Brier score of 0.14 in the external testing set. In addition, the limitations of the traditional staging system were revealed, and a personalized survival prediction system based on our risk scoring grouping was developed. Conclusions: Our study developed a deep neural network model for adenosarcoma. The performance of this model was superior to that of the traditional Cox proportional hazard model. In addition, a personalized survival prediction system was developed based on our deep survival learning model, which provided more accurate prognostic information for adenosarcoma patients.